The vertebrate fauna of the upper Permian of Niger—XI. Cranial material of a juvenile Moradisaurus grandis (Reptilia: Captorhinidae). Issue 5 (30th March 2022) - Sidor, Christian A.; Ide, Oumarou; Larsson, Hans C. E.; O'Keefe, F. Robin; Smith, Roger M. H.; Steyer, J.-Sébastien; Modesto, Sean P.
ABSTRACT: We describe two partial skulls of juvenile individuals of Moradisaurus grandis, a moradisaurine captorhinid from the upper Permian Moradi Formation of northern Niger. The juvenile skulls are less than half the length of the largest known skull of M. grandis, and differ in featuring a transversely narrow mandible, only five rows of maxillary teeth, a relatively larger orbit, a relatively taller skull, a cultriform process of the parasphenoid angled upwards at 20–30° from the basal plate, and reduced ossification of the braincase. Most of these features have been considered characteristic of the less derived members of the family (e.g., Protocaptorhinus pricei, Captorhinus laticeps ). Data from juvenile Moradisaurus allow us to amend a previous inference that the braincase of the holotype and largest known skull of the moradisaurine Labidosaurikos meachami is characterized by poor ossification: we infer instead that this skull is not skeletally mature and that the braincase would have fully ossified in larger, ontogenetically older individuals of this moradisaurine. An updated cladistic analysis of captorhinids yields Moradisaurus as the sister taxon to Gansurhinus + Rothianiscus, replicating the results of several previous analyses, but improving slightly the robustness of Moradisaurinae and the clade of Labidosaurus + Moradisaurinae with respect to previous work.